2021
DOI: 10.1007/s12011-021-02940-7
|View full text |Cite
|
Sign up to set email alerts
|

Circulatory Imbalance of Essential and Toxic Trace Elements in Pre-dialysis and Hemodialysis Patients

Abstract: The status of essential and toxic trace elements in patients with different stages of chronic kidney disease (CKD) is still unclear and not well characterized. The present study examined the circulatory levels of a wide panel of trace elements (Al, Cr, Mn, Co, Ni, Cu, Zn, As, Se, Rb, Sr, Cd, Pb, and U) in hemodialysis patients (HD group) and pre-dialysis patients with stage 3 CKD (PD group). Comparisons were made between groups of patients and healthy individuals from the control group (CG). The levels of Al, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(17 citation statements)
references
References 28 publications
5
10
0
Order By: Relevance
“…As CKD progresses, GFR decreases, leading to an imbalance of certain trace elements, and higher CKD stages are associated with increased levels of Cu and decreased levels of Zn ( 153 ). This suggests the Cu/Zn ratio could be used as a marker for early and late detection of renal failure ( 154 ). Elevated circulating Cu levels may be a causal risk factor for CKD ( 155 ), although there are varying reports of Cu concentrations in patients on HD, such as moderate Cu deficiency, high Cu levels, or Cu toxicity ( 156 ).…”
Section: Discussionmentioning
confidence: 99%
“…As CKD progresses, GFR decreases, leading to an imbalance of certain trace elements, and higher CKD stages are associated with increased levels of Cu and decreased levels of Zn ( 153 ). This suggests the Cu/Zn ratio could be used as a marker for early and late detection of renal failure ( 154 ). Elevated circulating Cu levels may be a causal risk factor for CKD ( 155 ), although there are varying reports of Cu concentrations in patients on HD, such as moderate Cu deficiency, high Cu levels, or Cu toxicity ( 156 ).…”
Section: Discussionmentioning
confidence: 99%
“…In their systematic review with meta-analysis, Tonelli et al ( 2009) reported lower Mn concentration in HD patients [21]. More recently, Almeida et al (2020) also found a significantly lower serum Mn concentration in HD patients, but Stojsavljević et al (2022) reported increased Mn concentrations [15,34]. It should be noted, as mentioned before, that 96% of circulating Mn is found in erythrocytes, leucocytes and platelets, while only 4% is present in plasma [32].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that HD patients are at an increased risk of trace element imbalances [15][16][17][18][19][20][21][22][23]. While the concentration of essential trace elements may be decreased due to the inflammatory nature of the disease [24][25][26], lower food intake due to uremic anorexia or dietary restrictions [27][28][29] or losses during dialysis sessions [30], the concentration of non-essential/toxic trace elements may be increased due to loss of ability to excrete them in urine [31], among other factors.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Zn is an essential trace element in the human body, which has anti-inflammatory and anti-oxidant effects [ 149 , 150 ]. Zn deficiency is common in dialysis patients [ 148 , 151 ]. In 2009, Sahin et al.…”
Section: Advances In Research On Trace Elements and Malnutritionmentioning
confidence: 99%